The impact of lifestyles on the periodontal health of adults in Udupi district: A cross sectional study - Nishu Singla; Shashidhar Acharya; Ramprasad Vasthare Prabhakar; Kalyana Chakravarthy; Deepak Singhal; Ritesh Singla (Wolters Kluwer Medknow Publications, 2016)
Objectives: (1) To assess the impact of different lifestyle factors on periodontal health of adults. (2) To assess the impact of overall/combined lifestyle variable (calculated by health practice index [HPI]) on periodontal health of adults. Materials and Methods: A cross-sectional study consisting of a structured questionnaire on HPI, oral health-related behavior, and personal habits as well as sociodemographic variables was conducted on 800 subjects aged 20-50 years attending dental outreach set-ups of Manipal College of Dental Sciences, Manipal. Clinical examination for periodontal status was done by recording loss of attachment scores using community periodontal index (FDI/WHO-1982). Statistical analysis was done by bivariate analysis using Chi-square followed by multivariate analysis to obtain adjusted odds ratio with 95% confidence interval. Results: After adjusting for all the confounding variables in multivariate logistic regression analysis, the variables that showed an independent association with periodontitis were age, location, marital status, smoking, hours of sleep per night, physical activity, and overall poor lifestyles. Conclusion: Our results support studying a combined approach using various lifestyle behaviors for controlling chronic periodontitis. Necessary public health action on conditions which determine unhealthy lifestyle behaviors across population is needed which is possible by patient's involvement in self-care by promoting healthy lifestyles.